At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Solve for
n,
if
3n +1 – 4n – 14 = 5 (n + 1).


Sagot :

Answer:

n = -3

Step-by-step explanation:

Add like terms on the left side of the equation:

3n + 1 – 4n – 14 = 5(n + 1)

-n - 13 = 5(n + 1)

Distribute the 5:

-n - 13 = 5n + 5

Solve for n:

-6n - 13 = 5

-6n = 18

n = -3

So, the answer is n = -3

Answer:

Step-by-step explanation:

n = -3